Evaluation on the effects of 2D animation as a verbal apraxia therapy for children with verbal apraxia of speech - Rahim, Sarni Suhaila; Hidayat, Muhammad Taufik; Parumo, Shahril; A’bas, Nurul Najihah; Muhammad Sani, Muhammad ‘Ammar; Abdul Aziz, Hilmi (Science and Information Organization, 2022)
This article presents an evaluation of 2D Animation of Learning Numbers and Letters for Children with Verbal Apraxia. The developed application provides some knowledge and encourage children with verbal apraxia to learn and know about numbers and letters. An experimental testing was conducted to evaluate the usability of the developed application, aimed as a therapy for the children who suffer this apraxia across all age. Five important evaluation components such as learnability, usability, accessibility, functionality, and effectiveness were included in this testing to investigate the user engagement and satisfaction of the proposed medical and educational learning system. Online questionnaires were distributed as a method to collect user testing outputs. A total of 33 respondents from multimedia designers, practitioners, psychologists, and parents were involved in this survey. The results of the testing indicate that majority of respondents are satisfied with the outcomes of the 2D animation video. The results presented may facilitate improvements in the teaching syllabus for students with speech and language disorder and produce a great visual animation treatment to the users.